2018
DOI: 10.1111/gcb.14041
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale disturbance legacies and the climate sensitivity of primary Picea abies forests

Abstract: Determining the drivers of shifting forest disturbance rates remains a pressing global change issue. Large-scale forest dynamics are commonly assumed to be climate driven, but appropriately scaled disturbance histories are rarely available to assess how disturbance legacies alter subsequent disturbance rates and the climate sensitivity of disturbance. We compiled multiple tree ring-based disturbance histories from primary Picea abies forest fragments distributed throughout five European landscapes spanning the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 67 publications
(182 reference statements)
1
69
0
Order By: Relevance
“…S17 and Temperli et al 2013) and influence the future stability of ecosystems (Schurman et al 2018). Our results indicate that increasing the level of service provisioning might at the same time reduce its temporal stability.…”
Section: Trade-offs Between Stability and Level Of Ecosystem Service mentioning
confidence: 74%
“…S17 and Temperli et al 2013) and influence the future stability of ecosystems (Schurman et al 2018). Our results indicate that increasing the level of service provisioning might at the same time reduce its temporal stability.…”
Section: Trade-offs Between Stability and Level Of Ecosystem Service mentioning
confidence: 74%
“…After correcting for age effects, growth rate fluctuations in Southern Romania appear more closely linked to known disturbances (asterisked on Figure 5; see also Schurman et al, 2018) and After correcting for age effects, growth rate fluctuations in Southern Romania appear more closely linked to known disturbances (asterisked on Figure 5; see also Schurman et al, 2018) and…”
Section: Northern Growth Rates Increasing With Rising Temperaturesmentioning
confidence: 99%
“…Tree age effects on BAI can confound growth trend analyses (Bowman, Brienen, Gloor, Phillips, & Prior, 2013) and known variability in the disturbance histories of each landscape implied the potential for age differences among landscapes (Schurman et al, 2018).…”
Section: Northern Growth Rates Increasing With Rising Temperaturesmentioning
confidence: 99%
“…Gravel, Beaudet, and Messier () reported synchronous understorey dynamics across southern Quebec since 1975 and postulated that it might have been triggered by an extreme climate event. Using the largest reported disturbance chronology in Europe (> 11,000 tree cores), Schurman et al () found that decadal disturbance rates varied unexpectedly for Picea abies forests and were likely to be driven by drought extremes. At time‐scales approaching a century, past disturbance events in European forests have also led to either an increase (Schurman et al, ) or a decrease in the susceptibility of a forest landscape to subsequent disturbance (Thom, Rammer, Garstenauer, & Seidl, ).…”
Section: Insights From Characterizing Forest Dynamics At Larger Scalesmentioning
confidence: 99%
“…Using the largest reported disturbance chronology in Europe (> 11,000 tree cores), Schurman et al () found that decadal disturbance rates varied unexpectedly for Picea abies forests and were likely to be driven by drought extremes. At time‐scales approaching a century, past disturbance events in European forests have also led to either an increase (Schurman et al, ) or a decrease in the susceptibility of a forest landscape to subsequent disturbance (Thom, Rammer, Garstenauer, & Seidl, ). A fire‐scar network in the western USA elucidated the first link between Pacific Ocean sea surface temperature variability and wildfire variation caused by drought (Swetnam & Betancourt, ).…”
Section: Insights From Characterizing Forest Dynamics At Larger Scalesmentioning
confidence: 99%